The impact of mortgage interest tax relief in the Netherlands, Sweden, Finland, Italy and Greece - Manos Matsaganis; Maria Flevotomou (University of Essex, Institute for Social and Economic Research (ISER), 2007)
Fiscal welfare, i.e. the use of the tax system to achieve social policy goals, is assuming ever greater importance throughout Europe and beyond. In housing, the favourable tax treatment of mortgage interest repayments has often coexisted alongside public programmes of housing benefit or social housing. Although the distributional effects of tax expenditure are known to be regressive, the issue has remained relatively under-researched. The paper uses the European tax-benefit model EUROMOD to quantify the distributional impact of mortgage interest tax relief in five European countries: the Netherlands, Sweden, Finland, Italy and Greece. The analysis reveals that higher-income groups capture a disproportionate share of total expenditure on mortgage interest tax relief in all countries, and that this effect is most regressive in the Netherlands and least regressive in Sweden. The paper concludes with a discussion of results and their policy implications.
Keywords: H23; I38; R21; 330; tax relief; mortgage repayments; inequality; microsimulation; Wohnungsbaufinanzierung; Hypothek; Steuerrechtliche Abschreibung; Einkommensverteilung; Simulation; Niederlande; Schweden; Finnland; Italien; Griechenland